Measuring the Stoichiometry of Functional PspA Complexes in Living Bacterial Cells by Single Molecule Photobleaching - Lenn, Tchern (2010)
We report a general method based on wide-field fluorescence imaging of single molecule photobleaching and Chung-Kennedy algorithm to measure the stoichiometry of functional protein complexes in living bacterial cells.